Case Report: Dostarlimab for treatment of aggressive cutaneous squamous cell carcinoma - Gandarillas, Sophia; Tang, Horace; Dasgeb, Bahar (Frontiers in Medicine, 2024)
Cutaneous squamous cell carcinoma (cSCC) is the second most common malignancy with the aggressive cSCC subtype being especially worrisome due to its higher metastatic and mortality rate. An 80-year-old immunocompetent Caucasian man presented with a locally advanced and recurrent cSCC for which he underwent six Mohs surgeries, radiation therapy, and standard immunotherapy treatments. Throughout treatment, the patient’s cancer continued to progress across different regions of the face. Biopsy and analysis were performed and showed that the cSCCs had a high mutational burden and oncogenes known to be present in tumors with aggressive nature. After the algorithmically applied standard of care failed to cure or control the progressing disease, the genetic analysis favored dostarlimab as a suitable option. With only three doses of 500 mg dostarlimab q3 weeks, the patient showed a fast response with macroscopic resolution of clinically discernible disease of, the previously noted, locally advanced cSCC on his right forehead, as well as other primary keratinocyte carcinomas on his left contralateral face, nose, left leg, and neck. This remarkable case can present an option for complex patients with locally advanced and recurrent cSCC who failed the current standard of care. Moreover, it warrants a proper clinical trial to assess efficacy and potential indication of dostarlimab in such patients. Of note is the presence of a KMT2D mutation and its well-identified correlation with mismatch repair deficiency (dMMR) and poor prognosis, which can play an informative role in clinical decision making and precision therapeutic choice at the point of care.